Two wrongs make a right? The politicization of trade policy and European trade strategy. Issue 12 (2nd December 2019) - Young, Alasdair R.
ABSTRACT: Since 2014 the (relatively) calm waters of the EU's trade policy have been roiled by wide-spread popular opposition to the EU's trade negotiations with the United States and Canada and the apparent spread of anti-globalization populism. The Commission's 'balanced and progressive' trade strategy is a response to these developments. This article assesses whether the response is adequate. It concludes that the strategy is unlikely to address the identified problem, because it largely reflects continuity with past practices that did not prevent or resolve the politicization of trade policy. It also concludes that the Commission's assessment of the politicization of trade policy is exaggerated. Thus, two wrongs may have produced the 'right' policy, at least in the narrow sense that EU trade policy is unlikely to be as politically fraught in future.